Nutritional Status and Hygiene Practice among Ethnic Communities in Selected Area of Bangladesh - Haque, Md Monoarul; Banu, Bilkis; Islam, Khaleda; Islam, ASM Mazharul; Islam, Mohammad Abu Naser (Bangladesh Journal of Nutrition, 2014)
Malnutrition is a common problem in Bangladesh. Nutritional status is a sensitive indicator of community health. The study was done to assess the nutritional status and hygiene practice among ethnic communities in Bangladesh. It was a Cross sectional study. The subjects were selected purposively. This study was conducted at sadar upazilla of Bandarban district in Chittagong division. Nutritional status was measured anthropometrically using body mass index according WHO classification and socioeconomic information, hygiene practice were presented as descriptive statistics (mean, standard deviation, frequency, percentage). Anthropometric data such as height and weight of the study subjects were collected by standard techniques to calculate body mass index. Statistical analyses were performed by appropriate univariate and multivariate techniques using SPSS windows 11.5 version. A total of 227 study subjects aged (Mean±SD) 35±15 years were studied. Among the study subjects majority of the tribal population were Marma (52%) and rest of were Bavrai (21%), Murong (18%), Tripura (3%), Khyang (3%), Tanchyanga (2%) and Chak (1%). Among the study subjects, most of the respondents (62%) were found normal in their nutritional status, 18% found underweight, 14% were overweight and only 6% were obese. Forty one percent of respondents were used to washing their hand with soap before taking meal but rest of the respondents (59%) were found to wash their hand only with water before taking their meal and 59% of the respondents washed their hand with soap after toilet. All the study subjects were found to wash their hand before preparing food and to wash their utensil. A smaller number of respondents (34%) were found to practice reheating their foods before serving. As outcome of better nutritional and hygiene status, majority (89%) of respondents were found to have no disease during the last two weeks of interview. Though nutritional status and hygiene practice among tribal population in selected area of Bangladesh are apparently satisfactory, as revealed in present study still there remain some lacking in this segment. Therefore, a more effective and targeted health and nutrition education program focusing nutrition and hygiene among our tribal population deserves to be suggested for implementation. Bangladesh J. Nutr. Vol. 26-27, December 2014, P: 87-94